Pembuatan Edible Film dari Karagenan Rumput Laut Eucheuma cottonii untuk Mengawetkan Buah Nanas - Harsa Pawigya (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Edible film is a thin layer that is made from an edible material and usually used as food coating or in between food components to prevent migration of water vapor, oxygen, carbon dioxide, aroma, and food lipid (such as anti-oxidant, anti-microbes, flavor,etc) and or fix the integrity mechanism and food characteristic. This article will explain about: (1) The optimum time for seaweed extraction; (2) The optimum amount of CMC addition at the process of making edible film. There are five kinds of different time used for the seaweed extraction, 0,25 hour; 0,5 hour; 1 hour; 1,5 hour; 2 hour. And five different CMC concentration (0,5%, 0,75%, 1%, 1,25%, 1,5%). The optimum time for the extraction is 0,5 hour with 22,2570 grams of carrageenan produced. The carrageenan produced willbe turned into edible film with a variation of CMC concentration. The edible film will be tested with weighted shrink test, color change, tensile strength test, and extension. It is found as a result of the research that the edible film which made from a carrageenan for 0,5 hour and 1,5% of CMC concentration has the best capability to preserve a pineapple. The edible film that could preserve a pineapple the longest has 19,61N tensile strength and 3,34 mm extension. The higher concentration of CMC used, the tensile strength will be less, longer it could extend.